(3CSfi GdeWGdH aj TQM QhV GdWGdHs - (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdSfjcj GdeUQj GdTGaYqj, CHh jMji , J (B926 (3g` s; (3TQa GdOjf ESeGYjd Hf CHj HcQ Hf YHO Gddg Hf EHQGgje GdebQj GdTQLj GdMSjfj, GdTGhQj GdRHjOj Gdjefj,J (B837 (3g` s ((3eMeO GdfTQJi s)
(3ChdgG (B:s
(3Chdg eHJhQ hChd GdehLhO efg CKfGA cJGH GdLfGjGJ Hbhdg (B: ( (3fbdg GdCUd Yf GdYHGOi hCbQg , bGd GdRQcTi (B: (3hGdeQGO ef bhdge hde jXgQ CKQ s
(3BNQgG (B:s
(3BNQg cJGH CegGJ GdChdGO (B) (3bhdg dcf jYRQ HhWFgG Ef Yde GdJMQjc , hdG jMO dTHgg Gdedc Je GdLRA GdeHGQc s
(3GdfSNI HgG MhGTs
(3HBNQgG bQGAI HGdeSLO GdCbUi HGdbOS SfI (B966(3g`s
(3Ydi ghGeTgG ebGHdGJ hJUMjMGJs
(3cJH GdeJf HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3Gdabg GdTGaYjs